Musculoskeletal Ultrasound in the Emergency Department - Chianca, Vito; Di Pietto, Francesco; Zappia, Marcello; Albano, Domenico; Messina, Carmelo; Sconfienza, Luca Maria (Seminars in Musculoskeletal Radiology, 2020)
The skin, nerves, and tendons are superficial anatomical structures that can easily be investigated with an ultrasound (US) examination in the emergency department (ED). US evaluation is relatively underused in musculoskeletal evaluation when compared with other emergency applications, such as abdominal trauma, possible aortic aneurysm, and in the cardiovascular system. The aim of this article is to revise the main bone and soft tissue conditions that can be assessed using US in the ED.
Keywords: ultrasound; musculoskeletal; emergency department; trauma; diagnostic imaging